NURSING AND NURSING TEAM ROLE IN HELLP SYNDROME: A REVIEW STUDY (REMUNOM, 2025)
The HELLP Syndrome is characterized as a severe progression of pre-eclampsia, leading to elevated blood pressure, the development of edema, and the presence of protein in the urine after the twentieth week of pregnancy. Although its incidence is low, it requires careful attention due to its potential severity. The present study aimed to understand the importance and the role of nurses in this syndrome based on previously conducted research. Through a literature review, it was possible to infer that nurses and the nursing team play a fundamental role in multiple stages of care for patients with HELLP Syndrome. This includes the initial screening of signs and symptoms, the performance of physical and laboratory assessments, patient treatment, and continuous monitoring throughout the entire process, encompassing pregnancy, childbirth, and the postpartum period. Therefore, nursing plays a vital role in early detection, effective management, and comprehensive support for pregnant women affected by this condition, contributing to the reduction of complications and the promotion of maternal and fetal health. Thus, investing in continuous training and education is essential to improve clinical outcomes and the quality of life of patients with HELLP Syndrome.